2014
DOI: 10.1007/s11284-014-1208-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of annual spatial variations in forest production and crop yields at landscape scale in temperate climate regions

Abstract: Simulating regional variations in gross primary production (GPP) and yields of major land cover types is complex due to differences in plant physiological properties, landscape topography, and climate gradients. In our study, we analyzed the inter-annual and inter-regional variation, as well as the effect of summer drought, on gross primary production and crop yields of 9 major land uses within the state-funded Bioenergy Region Bayreuth in Germany. We developed a simulation framework using a process based mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Šiaudinis et al [22] harvested 13.1, 13.5, 11.1, 12.4 and 8.2 t DM ha −1 on the 3rd, 4th, 5th, 6th and 7th year of experiment, respectively. These values are similar to predicted yields from the PIXGRO model developed by Ruidisch et al [120] ranging from 12.7 to 23.3 t DM ha −1 y −1 over a 10 year period. From two six-year old plantations Schorpp and Schrader [121] In their literature review, Gansberger et al [78] noted a reduction in the yield of S. perfoliatum grown at high latitudes, explained by short growing season.…”
Section: Silphium Perfoliatum Yieldsupporting
confidence: 89%
See 1 more Smart Citation
“…Šiaudinis et al [22] harvested 13.1, 13.5, 11.1, 12.4 and 8.2 t DM ha −1 on the 3rd, 4th, 5th, 6th and 7th year of experiment, respectively. These values are similar to predicted yields from the PIXGRO model developed by Ruidisch et al [120] ranging from 12.7 to 23.3 t DM ha −1 y −1 over a 10 year period. From two six-year old plantations Schorpp and Schrader [121] In their literature review, Gansberger et al [78] noted a reduction in the yield of S. perfoliatum grown at high latitudes, explained by short growing season.…”
Section: Silphium Perfoliatum Yieldsupporting
confidence: 89%
“…However Franzaring et al [10] has highlighted that S. perfoliatum yields can increase when the crop is grown at high altitudes, perhaps because of the increased water availability. Hartmann and Lunenberg [81] in a study of S. perfoliatum yields across six locations across Bavaria, Germany, also identified water availability and nutrient-rich soils as a key determinant for high yields, and Ruidisch et al [120] found a similar correlation with the yields of S. perfoliatum in a modelling study increasing from lowland to highland sites in Germany. Schittenhelm et al [92] also highlight the importance of water availability obtaining 16.1 t DM ha −1 y −1 from irrigated plants and 10.8 t DM ha −1 y −1 from non-irrigated plants.…”
Section: Silphium Perfoliatum Yieldmentioning
confidence: 91%
“…This is referred to as joint production (Baumgärtner et al, 2001) that follows the laws of thermodynamics, including the material balance principle (Coelli et al, 2007;Nguyen et al, 2012). From an ecological point of view, this production process can be modelled using ecologically process-based models (Nguyen and Tenhunen, 2013;Ruidisch et al, 2014) in which all factors that have a direct influence on the production process can be included, for example, soil fertility and climatic variations. In this way it is of course possible to examine the effects of these direct factors on the production process (Tenhunen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, grasslands and annual summer crops such as maize and potato do not exhibit any apparent regional pattern in the simulations. The 2nd generation bioenergy crop exhibits significantly higher GPP and yields compared to the conventional bioenergy crop maize, suggesting that cultivation of S. perfoliatum should be increased for economic and environmental reasons (Ruidisch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Challenges have been also made for revealing soil microbial components in adjacent grasslands and to measure the soil structure by MRI . Leaf and canopy ecophysiological characteristics which are tightly linked with ecosystem productivity in the Takayama site (Noda et al 2015), atmospheric approach to reveal the temporal changes in carbon exchange between the atmosphere and forests (Ishidoya et al 2015), and model analyses to clarify the functional contribution of leaf and canopy phenology on forest carbon balance under current and future conditions or to evaluate the ecosystem services in the regional scale (Ruidisch et al 2015). Beside these achievements the research has also been made for soil biogeochemistry with respect to the carbon and nitrogen dynamics, ecophysiological role of tree sapflow and transpiration in forest water cycle, open field warming experiments on tree canopy photosynthesis and soil carbon dynamics, 'allocation flux' of carbon beginning from photosynthetic absorption to biomass growth and respiratory fluxes in plants and soil, and the cross-scale consequences of canopy phenology and its functions between stand and landscape scale on the mountainous area.…”
Section: Editorialmentioning
confidence: 99%